Study of LQR weight matrix on Cp-Max - Yan, Feifei (2016)
In this study the effect of the weights of an LQR controller into the design of a conceptual 10 MW offshore wind turbine is analyzed. First, a load analysis is performed in the multi-body based aeroelastic code Cp-Lambda at varying sets of controller weights. Then, different wind turbine rotors are designed at different set of LQR weights. A design improvement in terms of blade mass and blade cost is found, while changes in the cost of energy are limited. Two weight parameters, Q3 and R3I have large influence on wind turbine design. When Q3 is enlarged by 3 times, blade mass and cost can be reduced by 2.1% and 1.45% respectively with -0.01% change of CoE. When R3I is enlarged by 3 times, blade mass and cost can be reduced by 2.86% and 1.37% respectively with 0.009% change of CoE.